ISTRI SEBAGAI PENCARI NAFKAH UTAMA AKIBAT SUAMI TERKENA PHK DALAM PERSPEKTIF HUKUM ISLAM (STUDI TERHADAP PENGRAJIN KOPYAH DI DUSUN NGABLAK KECAMATAN BALONGPANGGANG KABUPATEN GRESIK) (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
In the husband and wife relationship husband has rights and likewise the wife has rights. Indonesia is currently facing the Covid-19 pandemic, the impact of this pandemic is termination of employment, resulting in termination of employment and making husbands unable to provide for the family so that wives have to work to meet family needs. From this phenomenon the researcher wants to examine how the perspective of Islamic law on wives as main breadwinners. The phenomenon of the wife as the main breadwinner is in Ngablak Hamlet, Balongpanggang District, Gresik Regency. The results of the study used a qualitative approach with the type of field research and data collection techniques used interviews, observation, and documentation. As long as the wife works and earns a living to meet the needs of the family according to the religious rules, the law is permissible. In accordance with the practice of the wife working as the main breadwinner in the family of Kopyah craftsmen in Ngablak Hamlet, Balongpanggang District, Gresik Regency, this has met the criteria of working according to sharia by prioritizing Islamic teachings.Keywords: main livelihood, work termination, islamic law